Behavior Rating Inventory of Executive Function in Preschool (BRIEF-P) and Attention-Deficit and Hyperactivity Disorders (ADHD): A Systematic Review and Meta-Analysis of Floor and Ceiling Effects - Esperanza Bausela-Herreras; Yurena Alonso-Esteban; Francisco Alcantud-Marín (MDPI AG, 2023)
Background. ADHD is a neurodevelopmental disorder that is accompanied by executive challenges. Objectives. To obtain evidence of the usefulness of the BRIEF-P and to analyze the possible ceiling and floor effect of its scores in the assessment of executive function in preschoolers with signs compatible with a possible diagnosis of ADHD. Method. A search was performed in Science Direct, NCBI (PubMed), and ProQuest Education Journals during the period 2012-2022. We included studies that evaluated samples of individuals with symptomatology compatible with ADHD, with an age range between 2 and 6 years, published in English or Spanish. Of a total of 2538 articles, only seven met the inclusion criteria. The risk of bias was assessed using the QUADAS-2 questionnaire. The main variables were age and executive functioning. Conclusions. Executive deficits in early-age individuals with symptoms compatible with ADHD are more extensive than just deficits in working memory. A floor effect has been found in tests associated with hot executive functions and a ceiling effect in cold executive functions. This makes it necessary to use different tests to assess executive performance in preschoolers with ADHD-compatible symptomatology and to design intervention proposals accordingly. The BRIEF-P is an instrument that facilitates obtaining a sensitive and discriminative executive profile, although it should be used in combination with other neuropsychological performance tests.